Oral pre-exposure prophylaxis implementation in South Africa: a case study of USAID-supported programs - Milimu, Jerome Wendoh; Parmley, Lauren; Matjeng, Mahlodi; Madibane, Mathata; Mabika, Mandisi; Livingston, Jacques; Lawrence, Joseph; Motlhaoleng, Orapeleng; Subedar, Hasina; Tsekoa, Rethabile; Mthembu, Zandile (Frontiers in Reproductive Health, 2024)
Since the introduction of oral pre-exposure prophylaxis (PrEP) in 2016, countries have successfully scaled-up PrEP to populations at risk of HIV acquisition, including key populations, serodiscordant couples and pregnant women. Between 2016 and 2023, there were over 5.6 million oral PrEP initiations globally. Of these, over 1.2 million occurred in South Africa, with nearly 700,000 implemented through USAID/South Africa's PEPFAR program. This case study uses WHO's Building Blocks for Health Systems Strengthening to describe USAID's oral PrEP program in South Africa, reporting experiences and lessons learned in 14 districts across 7 provinces. Key lessons include: (i) Substantial donor financial investment was critical for expanding oral PrEP in South Africa, but sustained leadership and investment from government stakeholders, such as the Department of Health and the National Treasury, have been essential for sustainability. Despite fluctuations in USAID funding, annual PrEP initiations have continued to increase in USAID-supported districts largely due to local leadership. (ii) Health information and supply chain systems required agility to monitor oral PrEP introduction and scale-up. When systems lacked agility, temporary solutions like the development of interim reporting tools were necessary. (iii) Integrating community-based and facility-based service delivery supported client-centered care. Nurses and lay health workers contributed to over 80% of the full-time equivalents supporting PrEP under USAID's human resources for health portfolio. (iv) Integrating sexual and reproductive health services with oral PrEP service delivery provided clients with comprehensive, client-centered care. (v) Other client-centered care included differentiated service delivery options, such as mobile and gazebo modalities, and expanded PrEP choice through implementation science activities for new PrEP products. (vi) USAID-supported PrEP initiations have been highest among females of reproductive age in the general population and men who have sex with men among key populations, priority populations in South Africa. As done in this case study, sharing best practices and lessons learned from USAID/South Africa's oral PrEP program can strengthen the implementation evidence base and inform more efficient PrEP service delivery, particularly as new PrEP products become available.